Management of Diversity in the Delivery of Public Services. A Reflection from the Policies of Housing in Andalusia - Fernández-Borrero, Manuela A; Borrego-Alés, Yolanda; Orgambídez-Ramos, Alejandro; Vázquez-Aguado, Octavio; Relinque-Medina, Fernando (Journal of Tourism, Sustainability and Well-being, 2015)
Based on the management of diversity’s implications on the provision of public services, this work reflects on the perception that groups with ethnic differentiation have over housing policies in Andalusia. Specifically, we present the results obtained through a questionnaire elaborated ad hoc from a project based on modeling socio-spatial social intervention in social housing in Andalusia. The most significant differences found in relation to the Andalusians who benefit from these politics are exposed, with differentiation of the Gypsy collective as well as the Group of Moroccan immigrants who have access to this type of housing. Despite the differences, the needs for action in the field of social housing are equal for everyone in the neighborhood, despite ethnic diversity, although their perceptions, valuations and satisfaction can influence actions that are developed and must be considered. Finally, we believe that the politics of public housing in Andalusia expires with the social function of the housing. The problems reside in improving the management of this public park to achieve a major implication of the tenants in the maintenance of the communities and to promote new public housings that they could answer to the situations supervened in this context of crisis.